Childhood acquired brain injury: the knowledge and training needs of special educational needs coordinators. Issue 2 (13th July 2022) - Bennett, Emily; Thomas, Shirley; Woolf, Emma
Abstract : The aim of this study was to further explore Special Educational Need Co‐ordinators' (SENCos) knowledge of childhood acquired brain injury (ABI) and if they have received training on how to effectively support children and young people (CYP) with an ABI in school. SENCos from Nottinghamshire were asked to complete a survey face‐to‐face or online. Data reported by Howe and Ball ( Support for Learning, 32, 1, 85–100), was also used to allow comparisons between different counties in the UK for knowledge of childhood ABI. Results indicated that SENCos from Nottinghamshire hold numerous uncertainties about childhood ABI, although less uncertainties than SENCos from the West Midlands. A majority SENCos from Nottinghamshire had not received training about childhood ABI. Additional challenges in supporting CYP with an ABI were also identified. The findings show a clear need for more training on childhood ABI across UK schools. It is also apparent that obtaining funding for CYP with an ABI can be a challenge for SENCos. However, further research is needed to determine what these barriers to funding are.